Outcome of treatment with modified Ponseti technique in atypical congenital talipes equinovarus - Gupta, Sanjeev; Bhutt, Farooq; Kumar, Manoj; Ahmad, Maneer (International Journal of Research in Medical Sciences, 2020)
Background: The atypical congenital talipes equinovarus (CTEV) patients tend to have a different clinical foot presentation with small great toe, deep transverse crease of sole, tender swollen dorsum of foot and rigid equinus. Methods: This study was conducted in GMC Jammu to evaluate efficacy of modified Ponseti technique in atypical CTEV patients. It was a prospective study and the patient data was collected during OPD visits of patients from August, 2018 to June, 2020. Twenty-one patients were diagnosed as atypical CTEV and were managed with modification of conventional Ponseti technique and percutaneous release of achilles tendon was done in all patients. Three patients were lost to follow-up. Hence, the final number of study participants was 18 (n=18). Results: With modified Ponseti technique, functional correction was achieved in all the patients in our study. The average number of casts required was 8 (range; 5-10). At final follow-up visit, all feet are functionally corrected. Only one case of relapse was seen. Conclusions: Early diagnosis and treatment with modified Ponseti technique is an effective and easy method of treatment in atypical CTEV.